1999
DOI: 10.2527/1999.77102781x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postruminal supplementation of methionine and lysine, isoleucine, or all three amino acids on intake and chewing behavior, ruminal fermentation, and milk and milk component production.

Abstract: Four multiparous Holstein cows were fed a basal diet balanced with the Cornell Net Protein and Carbohydrate System (CNCPS). Diets were formulated to be co-limiting in intestinally absorbable supplies of methionine, lysine, and isoleucine. Cows were supplemented with no amino acids (control); lysine and methionine in a ruminally protected form; isoleucine by abomasal infusion; or lysine, methionine, and isoleucine in a 4x4 Latin square arrangement of treatments with 28-d periods. Performance of cows on all trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…Seymour et al, 1990;Kudrna et al, 1998;Robinson et al, 1999). Similarly in our study, the milk protein content and yield were significantly higher when both Met and Lys were supplemented compared to the control (P < 0.05).…”
Section: Milk Yield and Compositionsupporting
confidence: 67%
See 2 more Smart Citations
“…Seymour et al, 1990;Kudrna et al, 1998;Robinson et al, 1999). Similarly in our study, the milk protein content and yield were significantly higher when both Met and Lys were supplemented compared to the control (P < 0.05).…”
Section: Milk Yield and Compositionsupporting
confidence: 67%
“…Schwab et al, 1992). In contrast, Blum et al (1999) or Robinson et al (1999) did not find any effect of RP Met and Lys supplementation on the intake of dry matter and its components. a,b means in the same row followed by different superscripts differ (P < 0.05) 1 treatments were as follows: C -control; L -control + supplemental Lys (11.7 g/day); M -control + supplemental Met (18.2 g/day); ML -control + supplemental Met and Lys (18.2 and 11.7 g/day, respectively) 2 Lys determined as LysHCl…”
Section: Nutrient Intakementioning
confidence: 60%
See 1 more Smart Citation
“…1b; Robinson et al 1999). Isoleucine infusion at 30 g d -1 into the abomasum of cows did not affect yields or contents of milk protein or fat, but lactose secretion, lactose percentage and overall milk yield were increased (Robinson et al 1999).…”
Section: Addition Experimentsmentioning
confidence: 99%
“…However, depending on parameters and assumptions of the mathematical model used to make the predictions of AA balance, different AA may appear to be undersupplied. For example, in an experiment in which Lys, Met and Ile were supplemented postruminally, Robinson et al (1999) found that CNCPS version 2.13A (O'Connor et al 1993) predicted those three AA were in deficient supply in the basal diet but Shield (Robinson 1998) predicted deficiencies of Arg, Ile and Lys instead. An experimental approach, which guarantees that milk composition responses will be due to improvement of AA balance, is to administer all AA postruminally as a positive control and then subtract from the mix considerable quantities of the single AA in question.…”
Section: Subtraction Experimentsmentioning
confidence: 99%